Beyond the Pandemic: A Review of the Persistent Impacts of COVID-19 on Nigeria’s Socio-Economic, Political and Health Landscapes - Obasa, Stephen Olufemi; Fayemi, Olanrewaju Emmanuel Fayemi (African Journal of Stability and Development (AJSD), 2025)
The COVID-19 pandemic has profoundly impacted Nigeria, affecting its socio-economic, political, and health landscapes with lasting repercussions. It has exposed weaknesses in the healthcare system, economy, and political structure, leading to severe consequences such as exacerbated poverty and unemployment, reduced economic growth, strained political relationships, increased healthcare burdens, and long-term health issues. The government’s response measures have often worsened the situation, presented governance challenges and diminished citizens’ trust. The economic fallout includes decreased consumption, depreciating investments, declining net exports, and increased government expenditure. Politically, the pandemic has led to low political participation, erosion of public trust, and strained relationships between citizens and the government. The healthcare system’s vulnerabilities are evident in the increased burden on healthcare services and the urgent need for improved health infrastructure. This review underscores the urgent need for proactive strategies to address these lingering impacts and for the enhancement of Nigeria’s resilience against future pandemics. It calls for a multidisciplinary approach to develop and implement effective policies and programmes that mitigate the consequences of COVID-19 and strengthen the country’s preparedness for future health crises.